Novel Intronic Mutations of TBK1 Promote Aberrant Splicing Modes in Amyotrophic Lateral Sclerosis - Lu, Ying-Qian; Chen, Jian-Min; Lin, Han; Feng, Shu-Yan; Che, Chun-Hui; Liu, Chang-Yun; Huang, Hua-Pin; Zou, Zhang-Yu (Frontiers in Molecular Neuroscience, 2022)
TANK-binding kinase 1 (TBK1) has been identified as a causative gene of amyotrophic lateral sclerosis (ALS) in the Caucasian population in 2015. Here, we sequenced for TBK1 variants in a cohort of 15 familial ALS (fALS) and 275 sporadic ALS (sALS) of Chinese origin by targeted next-generation sequencing. We identified one likely benign missense variant (p. Ser398Pro), two missense variants of uncertain significance (p. Ile37Leu and p. Tyr677Asn), and two novel heterozygous variants in introns of TBK1, c.1522-3T > G and c.2066 + 4A > G. We performed splicing assays through minigene plasmids and RNA pull-down assay to determine that the two substitutions of nucleotides disrupted the binding of the important splicing regulator hnRNPA1 and promoted aberrant pre-mRNA splicing modes. The c.1522-3T > G variant promoted nearly 50.0% of abnormal transcripts (3 different types of insertions and deletions (indels) in junction of intron 13-exon 14) and the c.2066 + 4A > G variant inhibited about 75.0% inclusion of exon 19, both causing premature stop codon and producing TBK1 protein without CCD2. Immunofluorescence analysis showed that the expression of TBK1 with intronic variants was lower since less TBK1 distribution was observed in HEK293T cells. Both patients carrying TBK1 c.1522-3T > G and c.2066 + 4A > G variants developed a rapidly progressive ALS, with a survival of 31 and 10 months, respectively. The frequency of loss of function (LoF) variants in TBK1 was 0.73% in sALS in our cohort. We emphasize that intronic sequencing and pre-mRNA splicing analysis cannot be ignored to demonstrate the complex mutational spectrum and pathogenesis of ALS.